2016
DOI: 10.1007/s00347-016-0296-7
|View full text |Cite
|
Sign up to set email alerts
|

Orbitale Komplikation einer akuten Sinusitis

Abstract: Bacterial orbital cellulitis is a life-threatening infection of the postseptal orbital tissue. It can occur in the context of sinusitis, particularly in children and adolescents. Ocular complications include exposure keratopathy, increased intraocular pressure, occlusion of the central retinal artery or vein and optic neuropathy. Rarely, a subperiosteal abscess can occur, and osteomyelitis can lead to spread of the infection to the cerebrum. A rapid diagnosis and targeted therapy are essential for saving the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
2
1
1
Order By: Relevance
“…Thin-slice CT scan with contrast and MRI with fat suppression technique7 are very useful imaging methods in the case of orbital cellulitis for identifying the progression of disease, foreign bodies and the presence of subperiosteal abscess or intracranial involvement. Staphylococci and streptococci are the most common organisms in orbital cellulitis1,2 as in our case. Loss of vision8 occurs in more than 10% of patients including proptosis resulting in lagophthalmos and corneal exposure, mechanical compression of the optic nerve, severe increased IOP, orbital compartment syndrome, inflammation of the optic nerve and endophthalmitis.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Thin-slice CT scan with contrast and MRI with fat suppression technique7 are very useful imaging methods in the case of orbital cellulitis for identifying the progression of disease, foreign bodies and the presence of subperiosteal abscess or intracranial involvement. Staphylococci and streptococci are the most common organisms in orbital cellulitis1,2 as in our case. Loss of vision8 occurs in more than 10% of patients including proptosis resulting in lagophthalmos and corneal exposure, mechanical compression of the optic nerve, severe increased IOP, orbital compartment syndrome, inflammation of the optic nerve and endophthalmitis.…”
Section: Discussionsupporting
confidence: 60%
“…The most common pathogens are Gram-positive bacteria such as Streptococc us spp. and Staphylococcus aureus 1,2. Fungal infections should be considered in immunocompromised patients.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to our series, where the ophthalmological complications of rhino-sinusitis were dominated by pre septal cellulitis and pre septal abscess, Bejor UN et al [10] found exposure keratopathy, increased intraocular pressure, central retinal artery or vein occlusion and optic neuropathy as ocular complications. This confirms the hypothesis that the types of complications vary according to the initial anatomical involvement, which was mainly maxillary and ethmoid in our series.…”
Section: Discussioncontrasting
confidence: 99%
“…By contrast, the patient presented in this article recovered visual acuity from NLP postoperatively to 20/20 despite infection-related and/or surgery-related optic nerve injury evident on OCT. Consistent with previous observations in optic neuropathy secondary to severe pediatric infections (5), our patient recovered relatively rapidly compared with adults with SBO (3). However, complete recovery of central visual acuity from NLP is remarkable and likely reflects the lack of systemic comorbidities, surgical accessibility of the infectious source, and timely intervention.…”
Section: Discussionsupporting
confidence: 91%